2021
DOI: 10.1007/s10989-021-10211-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Peptide Inhibitors of ACE-2 Target of SARS-CoV-2 from Buckwheat & Quinoa

Abstract: It is well established fact that peptides from various foods offer human health benefits displaying diverse functionalities. Millets considered as super foods is a major alternative in recent days for traditional diet being rich in proteins and fibre along with trace minerals and vitamins. In this connection, proteins from Buckwheat and Quinoa were digested by in vitro simulation digestion for the generation of peptides, analyzed by nLC-MS/MS and the functional annotations of the identified proteins/peptides w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Of course, future experiments should be conducted to verify their inhibitory effects on three SARS-CoV-2 target proteins, bioavailability, toxicity, and allergenicity. Similarly, the quinoa peptides generated by in vitro digestion were served as a library for screening potential therapeutic targets for SARS-CoV-2 (Rangaswamy et al 2021). The results were that the peptide NWRTVKYG from quinoa presented favorable interactions with the binding site of angiotensin-converting enzyme-2 (ACE-2), a functional receptor for the SARS-CoV-2, and the molecular dynamic simulation revealed the ability of the peptide in stabilizing the protein-peptide composite.…”
Section: Profiles Of Potential Bioactivity Of Quinoa Peptides By In Silico Approachesmentioning
confidence: 99%
“…Of course, future experiments should be conducted to verify their inhibitory effects on three SARS-CoV-2 target proteins, bioavailability, toxicity, and allergenicity. Similarly, the quinoa peptides generated by in vitro digestion were served as a library for screening potential therapeutic targets for SARS-CoV-2 (Rangaswamy et al 2021). The results were that the peptide NWRTVKYG from quinoa presented favorable interactions with the binding site of angiotensin-converting enzyme-2 (ACE-2), a functional receptor for the SARS-CoV-2, and the molecular dynamic simulation revealed the ability of the peptide in stabilizing the protein-peptide composite.…”
Section: Profiles Of Potential Bioactivity Of Quinoa Peptides By In Silico Approachesmentioning
confidence: 99%
“…In contrast to treating food as a cornucopia of potentially therapeutic compounds as described above, some researchers have sought to screen for compounds that may be released by digestive enzymes after consumption. Studies using this approach assessed bioactive peptides released from dietary proteins from grains, seeds [ 49 , 50 ], and microalgae [ 51 ]; fish [ 52 ] and squid [ 53 ]; and soy cheese [ 54 • ]. While some studies followed the modern omics approach, wherein peptides are first isolated and identified in vitro using liquid chromatography and mass spectrometry [ 49 , 54 • ], most of these studies adopted an entirely in silico approach that used simulated gastrointestinal digestion to predict the resulting mixture of hydrolyzed peptides.…”
Section: Proteins May Release Antiviral Peptides After Digestionmentioning
confidence: 99%
“…Studies using this approach assessed bioactive peptides released from dietary proteins from grains, seeds [ 49 , 50 ], and microalgae [ 51 ]; fish [ 52 ] and squid [ 53 ]; and soy cheese [ 54 • ]. While some studies followed the modern omics approach, wherein peptides are first isolated and identified in vitro using liquid chromatography and mass spectrometry [ 49 , 54 • ], most of these studies adopted an entirely in silico approach that used simulated gastrointestinal digestion to predict the resulting mixture of hydrolyzed peptides. Also unlike contemporary bioactive peptide research, which typically focus on peptides as a purified end product [ 9 ], several studies listed here also considered the applicability of the source protein as nutritional interventions for COVID-19 patients [ 50 , 51 , 52 , 53 ].…”
Section: Proteins May Release Antiviral Peptides After Digestionmentioning
confidence: 99%
“…Quinoa protein has potential uses such as a novel bioactive peptide with anti-diabetic property [86]. In addition, peptide inhibitors of interaction of spike protein SARS-CoV-2 angiotensin converting enzyme-2, can be used as an effective strategy to treat patients with COVID-19 [94,95].…”
Section: Total Protein Content Globulins and Albumins Yield Efficiencymentioning
confidence: 99%